Local Agency and Complex Power Shifts in the Era of Belt and Road: Perceptions of Chinese Aid in the South Pacific. Issue 117 (4th May 2019) - Pan, Chengxin; Clarke, Matthew; Loy-Wilson, Sophie
ABSTRACT: Beijing's ambitious Belt and Road Initiative (BRI) has exacerbated a longstanding concern about the power shift from the West to China. The existing debate, however, is both motivated by, and fixated on, the strategic concerns of and about great powers (and to a lesser extent, middle powers). What is often overlooked is the concerns and voices of smaller countries and contested regions where some of the power-shift symptoms allegedly unfold, such as the South Pacific. To traditional donors such as Australia, the power dynamism in the South Pacific is largely a linear, two-way model of power shift from Western donors to Beijing. Challenging this model, this article proposes a complex, three-way model to bring small and seemingly passive actors into the power shift equation. To illustrate, the article uses Papua New Guinea's (PNG) perceptions of China's aid vis-à-vis Australia's aid as a case study. Relying mostly on primary (interview) sources, this study not only reveals some nuanced attitudes of local actors toward the great-power interactions, but also highlights the hitherto neglected role and agency of Pacific Island nations and their domestic politics in the inherently complex power shifts.